Moderating-mediating effect of religious spirituality and work engagement: antecedents of job performance - Novia Zahrah (2020)
The effectiveness of nursing practices resulting in decreasing patient waiting time, increasing patients’ satisfaction, as well as sustaining high-quality healthcare delivery as a whole. Thus, it is crucial to evaluate nurses’ performance in taking an active part to act quickly and effectively. Yet, patients’ satisfaction is no longer limited to diagnosis and treatment, but services and care they receive. Caring processes have a major influence in controlling patient experiences and formulating their expectations as well as their perceptions of nursing performance. Therefore, this study incorporated the caring process into nurses' performance criteria and aimed to recognize contributing factors to nurses’ job performance. Precisely, this study examines the relationship between workload (WL), supervisor support (SS), moral competence (MC), work engagement (WE), and job performance (JP). This study treated WE as a mediating variable between WL, SS, MC, and JP. This study also incorporated the moderating effect of religious spirituality (RS) on the relationship between WL, SS, MC, and WE due to the inconsistent findings of previous studies that were found. A quantitative research design was conducted. Data were collected from four general hospitals in Peninsular Malaysia using a cross-sectional method. 718 questionnaires were distributed to 718 Staff Nurses who were sampled using a non-proportional quota sampling technique. Smart-PLS 3.2.8 was used in testing the study hypotheses. The statistical results of this study indicated that only the direct relationship between MC and JP as well as the direct relationship between WL, SS, and MC on WE were supported. The result also supports the positive significant relationship between WE and JP. In terms of mediation effect, WE only mediate the relationship between SS, MC, and JP. While for the moderation results, RS was only found to have a significant moderating role in the relationship between SS and WE. Based on the findings, hospitals’ management should give more focus on nurses’ job demands-resources and personal resources to boost their work engagement as well as enhancing their job performance. Finally, the implications, limitations of the study, and future research direction were also discussed in this study.